COMMERCIAL RIGHTS AS A MAIN COMPONENT LIBERALIZATION OF ECONOMIC ACTIVITIES IN THE INDUSTRYAIR TRANSPORT - Bezzubov, Dmitry; Dobkina, Kateryna; Klyuyeva, Yevgeniya; Vitko, Oleksandr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to find ways to solve the problems of ensuring the commercial rights of aviation enterprises from the standpoint of the organizational, legal and economic component of the enterprise, to outline models for ensuring compliance with commercial rights in the activities of aviation enterprises, to develop a universal model for ensuring "freedom of air" in the activities of aviation enterprises during cargo transportation. Research methods: the basis of the scientific article is scientific methods and principles inherent in both the general theory of law and the science of international law with its specific features. In particular, comparative-legal, logical-legal and formal-legal research methods were used. Results: applied principles of economic activity of air carriers from the standpoint of norms of international air law have been formed. Ways of liberalizing access to the air transportation market and ensuring the economic viability of air carriers are outlined. International normative acts regarding the problems of legal provision of "freedom of the air" from the point of view of air transportation have been analyzed. It is claimed that there is a connection between the degree of liberalization and the economic efficiency of the aviation enterprise. For Ukraine, it is important to determine the optimal legal forms and mechanisms for the liberalization of access to the international air transport market in general, as well as to the EU air transport market. Discussion: the Chicago Convention and ICAO documents establish rules and procedures for the use of "air freedom" in commercial air transport. The legal provision of commercial rights to freedom of air transport is not limited to the norms of international law, but is also carried out at the level of decisions of competent state bodies and by concluding bilateral or regional agreements. There has been an ambiguous practice of applying ICAO norms regarding the commercial use of air transportation under the rules of "freedom of the air".